Career: a systematisation of perspectives and theoretical premises - Cybal-Michalska, Agnieszka (Kultura-Społeczeństwo-Edukacja, 2019)
The article offers various systematisations of career theories. In the most general spectrum of classification, two criteria can be found: the content of the theory: content theories; process theories; content-and-process theories, and the constitutive factors of career: prescriptive theories; lifecycle theories. The highlighted classifications of career theories integrate and synthesise accounts, whose structural contents indicate a variety of different sources and cognitive perspectives, constituting a review of the thought regarding the career development process in a particular historical context, as a time period in which they have been established. Various contexts of apprehending the career issue lead to changes in its “theorising”.